2012
DOI: 10.1515/nanoph-2012-0003
|View full text |Cite
|
Sign up to set email alerts
|

Low loss hollow-core waveguide on a silicon substrate

Abstract: Optical-fi ber-based, hollow-core waveguides (HCWs) have opened up many new applications in laser surgery, gas sensors, and non-linear optics. Chip-scale HCWs are desirable because they are compact, light-weight and can be integrated with other devices into systems-on-a-chip. However, their progress has been hindered by the lack of a low loss waveguide architecture. Here, a completely new waveguiding concept is demonstrated using two planar, parallel, silicon-on-insulator wafers with high-contrast subwavelengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 20 publications
(34 reference statements)
0
18
0
Order By: Relevance
“…In other words, lateral confinement is realized without any physical sidewalls! We experimentally demonstrated that its propagation loss is as low as 0.37 dB/cm [46], the lowest for HCW mode-matched to a single mode fiber. The second type of HCG HCW involves placing DBR on the side for lateral confinement.…”
Section: Chapter 3 High Contrast Grating Based Hollow-core Waveguide mentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, lateral confinement is realized without any physical sidewalls! We experimentally demonstrated that its propagation loss is as low as 0.37 dB/cm [46], the lowest for HCW mode-matched to a single mode fiber. The second type of HCG HCW involves placing DBR on the side for lateral confinement.…”
Section: Chapter 3 High Contrast Grating Based Hollow-core Waveguide mentioning
confidence: 99%
“…One of the applications is hollow-core waveguide, where high reflection mirrors are required for light confinement. By placing two HCGs in parallel [45,46], or four HCGs in a cage-like scheme, hollow-core waveguides can be made to provide two-dimensional light confinement [45,47]. On this hollow-core waveguide platform, novel functionalities such as low-loss slow light [47,48], ultra-compact optical coupler, splitter [49] and switch [50] can be realized with special HCG designs.…”
Section: Introduction To High Contrast Gratingmentioning
confidence: 99%
“…For practical application, lateral confinement is critical. Previously, we demonstrated a lateral confinement scheme by varying the HCG dimension laterally such that the effective index of the core is higher than that of the cladding [19]. This is a novel use of the effective index method in HCW.…”
Section: Hcm Waveguides and Couplersmentioning
confidence: 99%
“…Many extraordinary features were obtained with such simple structures. Notable accomplishments include HCG widely-wavelength-tunable VCSELs [11][12][13][14][15][16], HCG high-Q resonators [17,18], HCG hollow-core waveguides [19,20], HCG surface-normal couplers [21], and HCG high-NA planar lenses [22,23]. More recent advances include HCG phased arrays [24,25], surface-normal second harmonic emission from HCGs [26], flexible HCG metasurfaces [27], HCG VCSELs on silicon [28], 2D HCM tunable VCSELs [29], and metasurface holograms [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Since then ARROWs have found applications in lasers [30], single-molecule detection [31], and have been used to demonstrate electromagnetically induced transparency and slow light on a chip [6]. At the same time, an alternative approach to on-chip hollow-core waveguides, based on hollow core waveguides utilizing high-contrast subwavelength gratings (HCSWG), has been recently demonstrated by Yang et al [32]. While the reported propagation losses in these structures have been as low as 0.37 dB/cm, the waveguides have mode areas around 100 µm 2 for 9 × 11 µm sized cores, which is much larger than what has been achieved in ARROWs [33].…”
Section: Antiresonant Reflection Optical Waveguidesmentioning
confidence: 99%